Sistem Pendukung Keputusan Penentuan Balita Sehat Dengan Metode Simple Additive Weighting Di Desa Semuli Jaya - Afif Kholifah Muawanah; Rustam Rustam; Pakarti Riswanto; Supriyanto Supriyanto (Institut Bakti Nusantara, 2023)
The toddler period is a very important golden period in the process of human development, because in this period the ability to speak, creativity, social awareness, emotions, and intelligence develop very rapidly. Growth and development in infancy is a determinant of success in the quality of growth and development of children in the next period. The Simple Additive Weighting (SAW) method, which is often known as the weighted sum method, has several advantages compared to other methods. The advantage of the SAW method is that it can make a more precise assessment, based on predetermined criteria values and preference weights. Semuli Jaya Village Posyandu is an integrated health center located in Aabud Semuli District in the North Lampung Region. Based on the results and discussion of the calculation process for determining healthy toddlers using the Simple Additive Weighting (SAW) method at Posyandu Semuli Jaya Village, the results of Dasyu Ghanasi with a final score of 7,15 are ranked 1. However, it is important to note that the conclusion of the assessment of healthy toddlers can only be drawn after conducting a comprehensive analysis of the relevant data